Study of Nanoporous Carbon Fabrics for Rechargeable Energy Storage Capacitors. (21st May 2018) - Karabanov, Sergey M.; Litvinov, Vladimir G.; Rybin, Nikolay B.; Slivkin, Evgeniy V.; Oreshkin, Vladimir V.; Suvorov, Dmitriy V.
ABSTRACT: In this work, we present the results of investigation of the nanoporous material – carbon fabrics, which is used as electrodes in rechargeable energy storage capacitors (ultracapacitors). The impurity composition in the fabrics, the influence of thermal annealing conditions on the impurity concentration is studied. The performed studies resulted in determination of the investigated carbon material structure, determination of impurity composition of carbon material and change of impurity content depending on thermal treatment in vacuum at different temperatures and time intervals. The optimum temperature range for the treatment of carbon fabrics in vacuum that is important for its application in energy storage devices is found.